Huaier Effects on Functional Compensation with Destructive Ribosomal RNA Structure after Anti-SARS-CoV-2 mRNA Vaccination - Tanaka, Manami; Tanaka, Tomoo; Zhu, Xiaolong; Teng, Fei; Lin, Hong; Luo, Zhu; Pan, Ying; Sadahiro, Sotaro; Suzuki, Toshiyuki; Maeda, Yuji; Wei, Ding; Lu, Zhengxin (Archives of Clinical and Biomedical Research, 2022)
Although striking effects of vaccination strategy against COVID-19 world-wide, a long-term influence by sequential viral mRNA injections are unknown. We analysed biological alterations by total RNA sequencing in Pfizer-BioNTech vaccinated normal healthy volunteers and cancer patients, with or without adjuvant Huaier therapy. A significant destruction in ribosomal RNA structures was identified, enhanced by serial shots. Unlike the destruction caused by chemotherapy with platinum (II) complex, progressive destruction in 18S ribosome was identified even at 6 months after vaccination. The influence resulted in massive inhibition of translation and transcription, significantly in intra/inter neural signaling transfer and in lipid metabolism, related to ageing process. Huaier compensated these dysfunctions by miRNA-mediated transcriptional control, by typical activation in PI3K/AKT signaling pathway. Gene Ontology analysis revealed spontaneous virion production in number even after 3 months of the first vaccination. Present study indicated that the adjuvant therapy like Huaier compensates accelerated ageing process by mRNA vaccination.